Use of blackboard in Singapore Polytechnic. - Siaw, Ying Kwong. (2008)
The use of blackboard in Singapore Polytechnic was investigated in terms of the usage of IT supporting tools for e-learning. User's perceptions in terms of their familiarity and comfort levels were also studied.